The effect of PPR control and dipping on village goat populations in southwest Nigeria - Reynolds, L.; Francis, P. (1988)
A study conducted to determine the effect of PPR control and dipping on village goat populations in southwest Nigeria. Includes data on human and goat populations, herd structure, entries and exits, reproductive performance, monthly birth, purchases, mortalities, sales and loans-out.